Urinary Sediment mRNA Level of CREBBP and CYBA in Children With Steroid-Resistant Nephrotic Syndrome - Li, Wei; Shou, Xinyi; Xiang, Wenqing; He, Lin; Li, Lin; Fu, Haidong; Mao, Jianhua (Frontiers in Immunology, 2022)
Background: This study aimed to evaluate gene expression patterns in urinary sediment samples of children with steroid-resistant nephrotic syndrome (SRNS). Methods: The messenger RNA (mRNA) levels of 770 immune-related genes were detected using a NanoString nCounter platform. To verify the NanoString results, quantitative analysis of nine gene mRNAs was performed using real-time RT-PCR in more samples. Results: Firstly, compared with the steroid-sensitive nephrotic syndrome (SSNS) group (n=3), significant changes were observed in the mRNA level of 70 genes, including MAP3K14, CYBA, SLC3A2, CREB-binding protein (CREBBP), CD68, forkhead box P1 (FOXP1), CD74, ITGB2, IFI30, and so forth, in the SRNS group (n=3). A total of 129 children with idiopathic nephrotic syndrome (INS), 15 with acute glomerulonephritis, and 6 with immunoglobulin A nephropathy (IgAN) were enrolled to verify the NanoString results. Compared with patients with IgAN, those with INS had significantly lower levels of FOXP1 (P=0.047) and higher levels of CREBBP (P=0.023). Among SSNS, the mRNA level of ITGB2 was significantly lower in the non-relapse group than in the non-frequent relapse and frequent-relapse groups (P=0.006). Compared with the SSNS group, CREBBP was significantly elevated in the SRNS group (P=0.02). Further, CYBA significantly decreased in the SRNS group (P=0.01). The area under the curve (AUC) for CREBBP and CYBA was 0.655 and 0.669, respectively. CREBBP had a sensitivity of 83.3% and a specificity of 49.4% and CYBA had a sensitivity of 58.3% and a specificity of 83.1% to rule out SSNS and SRNS. The diagnosis value was better for CREBBP+CYBA than for CREBBP or CYBA alone, indicating that the combination of CREBBP and CYBA was a more effective biomarker in predicting steroid resistance (AUC=0.666; sensitivity=63.9%; specificity=76.4%). Conclusions: This study was novel in investigating the urinary sediment mRNA level in children with INS using high-throughput NanoString nCounter technology, and 70 genes that may relate to SRNS were found. The results revealed that the urinary sediment mRNA level of ITGB2 was significantly lower in the non-relapse group than in the non-frequent relapse and frequent-relapse groups. Meanwhile, CREBBP was significantly elevated and CYBA was significantly lowered in the SRNS group compared with the SSNS group.